2022
DOI: 10.3389/fnins.2022.917752
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Anesthesia Methods on the Treatment of Parkinson’s Disease by Bilateral Deep Brain Stimulation of the Subthalamic Nucleus

Abstract: BackgroundSubthalamic nucleus deep brain stimulation (STN–DBS) surgery for Parkinson’s disease (PD) is routinely performed at medical centers worldwide. However, it is debated whether general anesthesia (GA) or traditional local anesthetic (LA) is superior.PurposeThis study aims to compare the effects of LA and GA operation methods on clinical improvement in patients with PD, such as motor and non-motor symptoms, after STN–DBS surgery at our center.MethodA total of 157 patients with PD were retrospectively ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…Witt found a significant improvement in anxiety scales at 6-month follow-up after STN-DBS ( Witt et al, 2008 ). Our study found greater improvement in depression and anxiety postoperatively in asleep group than in awake group, which is consistent with Lu et al (2022) .…”
Section: Discussionsupporting
confidence: 91%
“…Witt found a significant improvement in anxiety scales at 6-month follow-up after STN-DBS ( Witt et al, 2008 ). Our study found greater improvement in depression and anxiety postoperatively in asleep group than in awake group, which is consistent with Lu et al (2022) .…”
Section: Discussionsupporting
confidence: 91%
“…Our statistical analysis revealed that STN-DBS Table 1 The demographic characteristics and clinical data of the included studies. Lu et al [14] 24 MER 63. [16] 6 MER 58 ± 6.1 59 ± 8 67 13.5 ± 2.6 13.4 ± 3.7…”
Section: Discussionmentioning
confidence: 99%